Analisa Docking Cyanidin 3,5-di-(6- malonylglucoside) terhadap Reseptor Plasmodium falciparum Enoyl Acyl Carrier Protein Reductase (PfENR) sebagai Anti Malaria - Nya Daniaty Malau; St Fatimah Azzahra (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2019)
Various efforts were made to develop a more effective discovery of malaria drugs. One of them is by utilizing computer technology. The use of computers in the discovery of new drugs aims to improve the efficiency of simulation and calculation processes in designing drugs (drug design). The purpose of this study was to analyze Cyanidin 3,5-di- (6- malonylglucoside) compounds against the Plasmodium falciparum Enoyl Acyl Carrier Protein Reductase (PfENR) receptor as Anti Malaria. The research stages are first, the search for ligand and receptor compounds. Second, the preparation stage of ligand compounds and receptors. Third, the docking simulation stage uses vina autodock. Finally, the analysis stage of the docking results. The results of the study is Cyanidin 3,5-di- (6 malonylglucoside) ligand compounds that have good stability against the Plasmodium falciparum Enoyl Acyl Carrier Protein Reductase enzyme (PfENR. This can be seen from the low bond energy, which is -10.7 kcal / mol. Cyanidin 3,5-di- (6 malonylglucoside) ligand has a good bond between ligand and receptor to the stability of the Plasmodium falciparum Enoyl Acyl Carrier Protein Reductase enzyme (PfENR because there are 6 hydrogen bonds. 5 bonds between hydrogen and receptor and one bond between hydrogen and ligand The interaction between ligands and receptors that are also formed is stable seen in the hydrophobic interactions and electrostatic interactions formed.The residues that form hydrophobic interactions are ALA217, ALA319, LEU315, MET261, TYR277 and TYR111 residues, while the electrostatic bonds are residues ASP107, SER317, SER215, GLY106 and LYS285 From this interaction it can be seen that the Cyanidin 3.5 ligand -di- (6 malonylglucoside) is stable to be used as an inhibitor of the Plasmodium falciparum Enoyl Acyl Carrier Protein Reductase (PfENR) enzyme. From some parameter analysis above, it can be concluded that Cyanidin 3,5-di- (6 malonylglucoside) ligand compound has good stability as an antimalarial drug candidate. Keywords: docking, drug design, ligan, reseptor